Особенности формирования структуры и свойств малоуглеродистой стали при теплой винтовой экструзии - Завдовеев, А.В. (Физика и техника высоких давлений, 2013)
Рассмотрены особенности формирования структуры и свойств малоуглеродистой стали, подвергнутой теплой винтовой экструзии (ВЭ). Методом дифракции обратнорассеянных электронов показано, что теплая ВЭ малоуглеродистой стали приводит к увеличению изотропности структуры, к значительной фрагментации и активации механизмов полигонизации, динамической рекристаллизации и зернограничному проскальзыванию. Данные структурные особенности позволили повысить прочность материала в 1.5 раза с сохранением высокого уровня пластичности. Розглянуто особливості формування структури та власивостей маловуглецевої сталі при теплій гвинтовій екструзії (ГЕ). Методом дифракції зворотньорозсіяних електронів показано, що тепла ГЕ маловуглецевої сталі призводить до збільшення ізотропності структури, значної фрагментації та активації механізмів полігонізації, до динамічної рекристалізації та зернограничного прослизання. Дані структурні особливості дозволили підвищити міцність матеріалу в 1.5 рази із збереженням високого рівня пластичності. The new developing technologies of metal formation based on simple shear are called severe plastic deformation (SPD). Their advantage is that they allow obtaining materials with unique complex properties combining high strength and plasticity as distinct from classical methods of metal forming. Numerous structural studies have been carried out for SPD-processed materials, such as Al, Ti, Cu and their alloys. Such complex systems as steels have not been adequately investigated because of labor intensive deformation processes. However, the studies are in progress. Due to insufficient knowledge of the structural changes occurring in low-carbon steels during SPD, there is a need for a more detailed consideration by modern methods. Thus, electron backscattered diffraction is a relatively new method, which allows a detailed study of the structure of metals. The paper discusses the characteristics of the formation of structure and texture of low-carbon steel subjected to warm twist extrusion (TE).